A Global Perspective on Firefly Extinction Threats. (3rd February 2020) - Lewis, Sara M; Wong, Choong Hay; Owens, Avalon C S; Fallon, Candace; Jepsen, Sarina; Thancharoen, Anchana; Wu, Chiahsiung; De Cock, Raphael; Novák, Martin; López-Palafox, Tania; Khoo, Veronica; Reed, J Michael
Abstract: Insect declines and their drivers have attracted considerable recent attention. Fireflies and glowworms are iconic insects whose conspicuous bioluminescent courtship displays carry unique cultural significance, giving them economic value as ecotourist attractions. Despite evidence of declines, a comprehensive review of the conservation status and threats facing the approximately 2000 firefly species worldwide is lacking. We conducted a survey of experts from diverse geographic regions to identify the most prominent perceived threats to firefly population and species persistence. Habitat loss, light pollution, and pesticide use were regarded as the most serious threats, although rankings differed substantially across regions. Our survey results accompany a comprehensive review of current evidence concerning the impact of these stressors on firefly populations. We also discuss risk factors likely to increase the vulnerability of certain species to particular threats. Finally, we highlight the need to establish monitoring programs to track long-term population trends for at-risk firefly taxa.